Pengaruh Iklan, Konformitas Dan Gaya Hidup Terhadap Perilaku Konsumtif Mahasiswa Menurut Etika Ekonomi Islam (Studi Kasus Pada Mahasiswa Jurusan Ekonomi Islam UINSU) - Hasibuan, Ismi Khoiriah; Harahap, Isnaini; Nasution, Juliana (Universitas Labuhanbatu, 2024)
This research is motivated by consumer behavior, namely students majoring in Islamic Economics UINSU in buying products / services.There are consumer behaviors that are not in accordance with the ethics of consumption in Islam.Consumptive behavior is a human tendency to consume without limits, where humans are more concerned with Wants than needs. Consumptive behavior is influenced by several factors, namely : advertising,conformity, and lifestyle.This study aims to determine the effect of advertising, conformity, and lifestyle on consumptive behavior in students majoring in Islamic Economics uinsu class of 2018. This study uses quantitative research methods.The subjects of the study were students of the Department of Islamic Economics uinsu class of 2018.Data collection using questionnaires with purposive sampling techniques.Respondents to this sample as many as 73 people.The results of the t-test concluded that the variables of advertising, conformity, lifestyle have a positive and significant effect on student consumptive behavior. Based on the ANOVA test, F-count obtained at 45,579 greater than F-table (2.73), it was concluded that advertising, conformity and lifestyle simultaneously affect the consumptive behavior of students majoring in Islamic Economics UINSU.Reviewed based on Islamic Economic ethics consumptive behavior that occurs in students majoring in economics is not in accordance with the theory of Islamic Economic ethics, especially Islamic consumption ethics because there are still some students who like to waste money by shopping not according to need or prefer desire.